Collaborative fashion consumption – A synthesis and future research agenda. (15th October 2021) - Henninger, Claudia E.; Brydges, Taylor; Iran, Samira; Vladimirova, Katia
Abstract: Collaborative consumption in the fashion industry has been put forward as a way to overcome current challenges of the 'take-make-use-dispose' economic system that is currently dominating the market, and has gained interest from practitioners, academics, and policy-makers. The purpose of this paper is to explore the state of collaborative fashion consumption research across various disciplines by critically reviewing and synthesizing this fragmented body of work. To do so, this systematic literature review critically evaluates where, how, and what research has been conducted on collaborative consumption in the fashion context, by further outlining gaps and a future research agenda. The paper reviews publications between 2004 and 2020 within peer-reviewed journals written in English, focusing on product service systems, access-based consumption, and collaborative consumption as key words. The analysis demonstrates that scholarly work addresses issues of terminology, attitudes, and motivations, specific modalities of engagement and practices of use and disposal, as well as business models that can help facilitate collaborative fashion consumption. The review also highlights that various gaps remain that require further enquiries, arguing that a deeper and more critical research agenda is required in order to provide a coherent terminology, better understand motivations to uptake collaborative consumption practices, as well as more cross-country analysis.